Studi Literatur: Peran Penting Literasi Membaca dalam Upaya Meningkatkan Karakter Positif Siswa Sekolah Dasar - Karimah, Aulia; Alfatikarahma, Nasywa; Fauziah, Afif (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to analyze the factors that cause low literacy in students. The methodology in this research uses literature study. The data collection technique is carried out by collecting secondary data which includes research results from articles, library sources and other documents relevant to this research. The sources used to collect data were journals obtained from Google Scholar, Garuda, and Sinta. The data analysis technique used is qualitative with stages including reducing data, presenting data, and concluding data. The research results show five student characters that need to be developed through literacy, including religious, nationalist, independent, cooperation and integrity.  Factors that hinder the literacy movement are the lack of reading materials, inadequate teacher resources, and limited facilities in schools. Meanwhile, the factors that support the literacy movement are the motivation of the school principal, the enthusiasm of the teachers, and the availability of libraries.